Empirisme dan Fenomenologis dalam Perspektif Filsafat Hukum Naturalism - Syafithri, Firda Nisa; Rahman, Fakhri Aulia; Piansah, Aip; Firmansyah, Diki (Lembaga Yasin AlSys, 2023)
Legal thought is characterized by the development of legal philosophy schools of thought. The emergence of a legal school was a response or criticism of the previous legal school, or it emerged as a response to the social development of society at that time. Currents that emerge and develop in the realm of legal thought include natural law, legal positivism (pure legal theory), utilitarianism, legal realism, American sociological jurisprudence, and schools of history. The entire history of legal philosophy makes it clear that the real problem in the field of legal philosophy is none other than this problem: what is natural law? From the beginning, natural law has been the subject of legal philosophy and until today this problem always reappears in people's minds. The research method that the writer uses in this research is descriptive analytic. The author uses data collection techniques in the form of a literature study by taking into account issues related to Empiricism and Phenomenology in the Legal Perspective of Naturalism. The research results have implications for the Legal Philosophy of Naturalism which can be seen in terms of empiricism and phenomenology. Based on the theory of natural law, there are those who argue that the beginning of all goods is not owned by anyone. Such goods are called ResNullius (See Article 519 BW. which states: